Text message : the centrality of scripture in preaching - Stackhouse, Ian; Crisp, Oliver (Lutterworth Press, 2014)
Preaching has fallen on hard times with many questioning its relevance and even its validity as a New Testament practice. This symposium of specially commissioned essays draws together an international team of thirteen scholars and pastors to address the importance of textual preaching in the history and life of the early church, the historic church, and the contemporary church. Contributions include essays on Old Testament preaching; preaching in Eastern Orthodoxy; gender-sensitive preaching; and preaching in the theology of Jonathan Edwards, Charles Spurgeon and Dietrich Bonhoeffer. It also.